2020
DOI: 10.1002/jpen.1869
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Decision Support System‐Assisted Pharmacy Intervention Reduces Feeding Tube–Related Medication Errors in Hospitalized Patients: A Focus on Medication Suitable for Feeding‐Tube Administration

Abstract: Background Administering medication through an enteral feeding tube (FT) is a frequent cause of errors resulting in increased morbidity and cost. Studies on interventions to prevent these errors in hospitalized patients, however, are limited. Objective The objective was to study the effect of a clinical decision support system (CDSS)–assisted pharmacy intervention on the incidence of FT‐related medication errors (FTRMEs) in hospitalized patients. Methods A pre‐post intervention study was conducted between Octo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Specifically, the skills of the hospital pharmacist, in the context of preventing errors in therapy, could play a key role in evaluating the correct and safe use of drugs, both in the prescription and in the administration phase. In fact, it has been already demonstrated that pharmacy intervention can significantly reduce the number of errors related to administering medication through the enteral feeding tube with minimal additional workload [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the skills of the hospital pharmacist, in the context of preventing errors in therapy, could play a key role in evaluating the correct and safe use of drugs, both in the prescription and in the administration phase. In fact, it has been already demonstrated that pharmacy intervention can significantly reduce the number of errors related to administering medication through the enteral feeding tube with minimal additional workload [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the high prevalence of enteral tube drug administration in the elderly population, which accounts for the majority of patients receiving home health care, initiatives are needed to reduce the risk of medication errors. Many studies have shown that a variety of methods, such as a thorough training program for medication administration through an enteral feeding tube with useful protocols for medical practitioners, strengthening the involvement of clinical pharmacists and dietitians in the home health care and hospital settings, and a software application for ordering and giving medicines that may notify staff to the presence of potential risk with ET administration and interaction, can signi cantly reduce the risk of errors in drug administration (13,(22)(23)(24)(25)(26) . On the other hand, for a considerable number of prescriptions, administration instructions for modifying medications to increase their consumption were missing.…”
Section: Discussionmentioning
confidence: 99%
“… Wasylewicz et al 26 Clinical decision support system-assisted pharmacy intervention reduces feeding tube-related medication errors in hospitalized patients: A focus on medication suitable for feeding-tube administration .…”
Section: Discussionmentioning
confidence: 99%